2012
DOI: 10.1107/s010827011202358x
|View full text |Cite
|
Sign up to set email alerts
|

XRD and VCD: a marriage of love or convenience? Honeymoon around a cyclic urea derivative

Abstract: The structures and absolute configurations of the enantiomers (3aR,8aR)-2,2-dimethyl-4,4,8,8-tetraphenyl-4,5,6,7,8,8a-hexahydro-3aH-1,3-dioxolo[4,5-e][1,3]diazepin-6-one 0.33-hydrate, C(32)H(30)N(2)O(3)·0.33H(2)O, (Ia), and (3aS,8aS)-2,2-dimethyl-4,4,8,8-tetraphenyl-4,5,6,7,8,8a-hexahydro-3aH-1,3-dioxolo[4,5-e][1,3]diazepin-6-one 0.39-hydrate, C(32)H(30)N(2)O(3)·0.39H(2)O, (Ib), have been elucidated unambiguously using the complementary power of single-crystal X-ray diffraction (XRD) and vibrational circular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Even though chiroptical spectroscopic methods have become highly popular, it has been demonstrated that it is important to use more than one method for determining the structure of chiral molecules . Therefore, in our problem pertinent information concerning chirality had to be inferred from the cooperative use of both XRD and VCD …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though chiroptical spectroscopic methods have become highly popular, it has been demonstrated that it is important to use more than one method for determining the structure of chiral molecules . Therefore, in our problem pertinent information concerning chirality had to be inferred from the cooperative use of both XRD and VCD …”
Section: Introductionmentioning
confidence: 99%
“…22 Therefore, in our problem pertinent information concerning chirality had to be inferred from the cooperative use of both XRD and VCD. 23 We report herein how the combination of both techniques was used to demonstrate that the rearrangement of enediynes, including only light atoms, proceeded as assumed with retention of configuration.…”
Section: Introductionmentioning
confidence: 99%